No can do modal verbs - Ilc, Gašper (ELOPE (Ljubljana), 2008)
The paper presents the systems of modal verbs in Slovene and English, and it focusses on comprehension and usage problems that advanced students of English may face when dealing with modal verb constructions. The paper identifies the key factors that give rise to various problems, such as in-vacuo vs. in-context treatment of modal verbs and absolute vs. relative temporal relations. It is argued that most students fail to fully understand contextualised modal verb constructions mostly due to the polysemy of modal verbs as well as their relative tense value. This is particularly the case when a (narrative) text containing modal verb constructions has a past time reference, and combines different narrative techniques.
Keywords: context; časovna referenčna točka; modal verbs; naklonski glagoli; narrative techniques; polysemy; prevajanje; pripovedni postopki; slovnični čas; sobesedilo; tense; time reference; translation; večpomenskost